Four years of IASI CO2 , CH4 , N2O retrievals: Validation with in situ observations from the Mauna Loa station - Masiello, Guido; Serio, Carmine; Venafra, Sara; Liuzzi, Giuliano; Camy-Peyret, Claude (Remote Sensing of Clouds and the Atmosphere XXIII, 2018)
IASI (Infrared Atmospheric Sounder Interferometer) soundings for the years 2014 to 2017 over sea surface for the Hawaii region have been used to retrieve column amount of CO 2 , CH 4 , N 2 O. The analysis allowed us to derive CO 2 , CH 4 and N 2 O growth rates, trend and seasonality, which have been compared to in situ observations from the Mauna Loa validation station. Day and night soundings have been used. During the day, for CO 2 and N 2 O we make specifically use of the IASI short wave band (2000 to 2250 cm -1 ), which is sensitive to sun radiation. Our forward/inverse module deals with sun radiation using a Cox-Munck model for the bidirectional reflectance distribution function. This makes it possible to exploit IASI soundings in sun-glint or close to sun-glint mode, which improves sensitivity of retrievals close to the surface. The analysis has been performed with our total IASI level 2 processor or τ 2 IP, which uses the whole IASI spectral coverage, therefore making it possible to exploit the whole information content of data. The code τ 2 IP also uses a random projection approach to reduce the dimensionality of the data space. Our analysis show that growth rate, trend and seasonality are extracted with high accuracy (we observe correlation with in situ data close or higher than 0.90). After validation, we have applied τ 2 IP to seven years of data over the Arctic sea basin and computed summer maps (July to September) of CO 2 and sea skin temperature. The results show that the increase of skin temperature parallels the increase of CO 2 column amount over the Arctic basin.